PENGEMBANGAN E-MODUL IPA BERBANTUAN FLIPPED CLASSROOM UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP - Siti Damaiyanti; Destien Atmi Arisandy; Yunita Wardianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a valid, practical, and effective e-module based on the flipped classroom model for the material on the human circulatory system. The research method employed is Research and Development (R&D) using the 4D development model (Define, Design, Develop, Disseminate). Research instruments included validity questionnaires, practicality questionnaires, and learning outcome tests. The findings indicate that the e-module is highly valid, with an average score of 4.75 from experts. Practicality reached the